Improving Students’ Vocabulary Mastery by Using Realia - Vina Sukrina (Universitas Negeri Medan, 2013)
ABSTRACTThis study was attempted to discover the improvement students‟ vocabulary mastery by using realia for elementary students‟ Grade IV. The objective of this study was to find out whether realia can significantly improve students‟ vocabulary or not. In this study, the writer was conducted by Applying Classroom Research. The subject of this study was one class of the grade IV students‟ of SD Negeri 060811 Medan which consisted of 36 students‟. The quantitative data were taken from vocabulary test as the instrument to find out the students‟ score. The qualitative data taken from diary notes and observation sheet describe the improvement of the students‟ vocabulary mastery of the students‟ vocabulary mastery was mostly improved in every test. The range of improvement of the first test and the last test was 83,33%. The observation sheet and the diary notes showed that the students‟ were interested in the teaching learning process. These finding show that there was an improvement on the students‟ vocabulary through realia that was supported by the result, the mean score of the second test (64,44) was better than mean score of first test (39,17), and the mean score of the third test (78,05) was better than the mean score of the second test. This implies that realia can be an alternative strategy in improving students‟ vocabulary mastery. It is suggested that realia to be used in teaching vocabulary especially to young learners.Keywords: Vocabulary Mastery, Realia Media, Procedure of Teaching Vocabulary.